2022
DOI: 10.1186/s41687-022-00498-z
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal and patient-reported outcomes following total hip arthroplasty: a longitudinal cohort study

Abstract: Background Total hip arthroplasty (THA) is a successful procedure that provides pain relief, restores function, and improves quality of life (QOL) for patients with advanced arthritis in their hip joint. To date, little research has examined the role of cognitive appraisal processes in THA outcomes. This study examined the role of cognitive appraisal processes in THA outcomes in the first year post-surgery. Methods This longitudinal cohort study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In contrast, the MCS showed notable but lesser improvement than the ODI over the first 12 months after surgery and then plateaued. These findings were similarly seen in a total hip arthroplasty population between a disease-specific outcome measure (the Hip Disability and Osteoarthritis Outcome Score [ 36 ]) and the MCS [ 37 ]. Of note, the relationship between these two outcomes varied over follow-up: they were uncorrelated at baseline and became more strongly correlated over time.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, the MCS showed notable but lesser improvement than the ODI over the first 12 months after surgery and then plateaued. These findings were similarly seen in a total hip arthroplasty population between a disease-specific outcome measure (the Hip Disability and Osteoarthritis Outcome Score [ 36 ]) and the MCS [ 37 ]. Of note, the relationship between these two outcomes varied over follow-up: they were uncorrelated at baseline and became more strongly correlated over time.…”
Section: Discussionmentioning
confidence: 75%
“…Findings revealed that specific appraisal processes, such as focusing on healthcare or living situation problems, were linked to worse outcomes in the initial six weeks post-THA. Conversely, other appraisal processes, like preparing one's family for health changes, correlated with improved outcomes during the same period [ 52 ]. In terms of short-term outcomes, a study examining the short-term results of total hip replacement (THR) identified patients experiencing functional recovery alongside those encountering treatment failure.…”
Section: Reviewmentioning
confidence: 99%